Cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy applications in upper and lower gastrointestinal cancer, a review - Drittone, Denise; Schipilliti, Francesca Matilde; Arrivi, Giulia; Mazzuca, Federica (Oncology Reviews, 2024)
Peritoneal metastases (PM) are the spread of tumor forms into the peritoneum as metastases from another organ. PM is a frequent condition in metastatic gastrointestinal cancer (colorectal, gastric, pancreatic, appendiceal, and cholangiocarcinoma); their presence confers a poor prognosis, reducing patient survival. The standard treatment consists of systemic chemotherapy according to current guidelines. In recent years, scientific evidence has shown how combined cytoreductive surgery (CRS) techniques followed by hyperthermic intraperitoneal chemotherapy (HIPEC) can improve survival in this patient population. Despite the results still obtained, using this combined technique is still under discussion. This review aims to highlight the benefits and limitations of this combined procedure, which is already widely used to treat peritoneal metastases in gynecological tumors.